Effects of conventional and alternating cushion weight-shifting in persons with spinal cord injury - Wu, Gary A. (J Rehabil Res Dev, 2014)
A repeated-measures study of 13 adult full-time wheelchair users with spinal cord injury (SCI) was carried out to determine whether alternating-pressure air cushion (APAC) use compared with independent pressure relief (IPR) provides reliable, effective pressure relief for individuals with SCI. Bilateral mean ischial interface pressure (IP), transcutaneous oxygen tension (T(c)PO(2)), and unilateral laser Doppler blood flow were evaluated. Blood flow component contributions were determined using short-time Fourier transform (STFT)-based spectral analysis. IPR assessment was carried out at recruitment. Study participants then used an APAC for 2 wk every 3 mo for 18 mo. IPR weight-shifting decreased mean ischial IP (p < 0.05) and increased mean T(c)PO(2) (p < 0.05). All variables rapidly returned to preintervention levels following weight-shifting except for the cardiac component of blood flow. APAC-induced weight-shifting decreased mean ischial IP (p < 0.05). Mean T(c)PO(2) increased and was higher than for IPR. STFT analysis indicated that quiet sitting following APAC-induced weight-shifting produced a higher neurogenic component of blood flow than following IPR (p = 0.02). Thus, IPR positively affects multiple aspects of tissue health but produces transient improvements and must be repeated regularly. APAC activation dynamically and continuously alters IP distribution with more sustained positive tissue health effects.